(untitled) (Experimental biology, 2021)
In this article, in the study of the anatomical structure of the roots, the identification of diagnostic signs is considered – perennial, herbaceous, very valuable medicinal plants Rhodiola rosea L, a species of the genus Rhodiola, the Crassulaceae family. In the future, we focus on the conservation and rational use of Rhodiola rosea L., one of the most valuable and rare medicinal plants, for the conservation of certain plant species, and replenishment of the genetic fund of this species. Rhodiola rosea L., popularly called the golden root, since the roots have a yellow golden color and have an ancient meaning in folk medicine.Despite the specific chemical composition, the official article in the State Pharmacopoeia of the Republic of Kazakhstan is not registered, primarily grows in Kazakhstan. The main objective of the study is to study the anatomical features of plants of Rhodiola rosea L. Based on the study, the anatomical features of the leaves, stems and transverse sections of the roots were identified, motor cells in the epidermis of the leaves, cleavage and concentration of tannins on the stems, the location of starchy crystals in the root rhytidoma, in the nucleus parenchyma were established. When determining the location of biologically active substances in Rhodiola rosea L., tannins were first detected in idioblasts.